2014
DOI: 10.1155/2014/941408
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Proteinuria in Hypertensive Disorders of Pregnancy

Abstract: Background. Progressive proteinuria indicates worsening of the condition in hypertensive disorders of pregnancy and hence its quantification guides clinician in decision making and treatment planning. Objective. To evaluate the efficacy of spot dipstick analysis and urinary protein-creatinine ratio (UPCR) in hypertensive disease of pregnancy for predicting 24-hour proteinuria. Subjects and Methods. A total of 102 patients qualifying inclusion criteria were evaluated with preadmission urine dipstick test and UP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…Generally, the estimation of 24 h urine proteins has been considered the gold standard for quantitation of proteinuria [7]. However, the collection of a 24 h urine sample is inconvenient for the patient and prone to pre-analytical errors, thereby leading to inaccurate results or variations in the application of the assay [8].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the estimation of 24 h urine proteins has been considered the gold standard for quantitation of proteinuria [7]. However, the collection of a 24 h urine sample is inconvenient for the patient and prone to pre-analytical errors, thereby leading to inaccurate results or variations in the application of the assay [8].…”
Section: Introductionmentioning
confidence: 99%
“…Nisell H et al in 2006 and Rathindranath R et al in 2015 suggested that in most cases the more cumbersome 24 hour urine collection can be replaced by the more convenient albumin/creatinine ratio on spot urine [8,9]. Amin SV et al in 2014 showed that area under curve for urinary protein: creatine ratio (UPCR) was 0.89 (95% CI: 0.83 to 0.95), it had sensitivity of 82% and false positive rate of 12.5% for cutoff value of 0.45 (Figure 2) [10]. They used higher cutoff values (1.46 and 1.83) for prediction of heavy proteinuria (2 g and 3 g/24 h, respectively).…”
Section: The Quantity Of Protein Loss Has Both Diagnostic and Prognostic Implications But What Constitutes An Ideal Test Or Cut Off Valuementioning
confidence: 99%
“…Protein excre on may vary during different mes of day but when divided by spot crea nine which is constant during the day, UPCR ra o forms a reliable indicator of proteinuria. It doesn't require admission, is convenient and reports are 6 available fast thus helping for early planning.…”
Section: Introductionmentioning
confidence: 99%